2019
DOI: 10.3390/polym11101692
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Titanium Dioxide Surface Modification on the Dispersion, Morphology, and Mechanical Properties of Recycled PP/PET/TiO2 PBNANOs

Abstract: Titanium dioxide (TiO2) nanoparticles have recently appeared in PET waste because of the introduction of opaque PET bottles. We prepare polymer blend nanocomposites (PBNANOs) by adding hydrophilic (hphi), hydrophobic (hpho), and hydrophobically modified (hphoM) titanium dioxide (TiO2) nanoparticles to 80rPP/20rPET recycled blends. Contact angle measurements show that the degree of hydrophilicity of TiO2 decreases in the order hphi > hpho > hphoM. A reduction of rPET droplet size occurs with the addition of TiO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 46 publications
(52 reference statements)
0
16
0
Order By: Relevance
“…34,35 Matxinandiarena et al showed that a good correlation was found between the crystallization rate of PET and the location of hydrophilic TiO 2 NPs, whereas the NPs resulted in the high PET crystallization rate. 15 They also found that the PET lamellar size and morphology were dependent on the NPs dispersion. Despite the studies on the weight fraction effect of NPs, more studies are still required to the mixing effects of hydrophilic and hydrophobic NPs on the thermomechanical properties of the nanocomposite.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…34,35 Matxinandiarena et al showed that a good correlation was found between the crystallization rate of PET and the location of hydrophilic TiO 2 NPs, whereas the NPs resulted in the high PET crystallization rate. 15 They also found that the PET lamellar size and morphology were dependent on the NPs dispersion. Despite the studies on the weight fraction effect of NPs, more studies are still required to the mixing effects of hydrophilic and hydrophobic NPs on the thermomechanical properties of the nanocomposite.…”
Section: Introductionmentioning
confidence: 98%
“…The proper performance of nanocomposites could be attributed to the type of polymer chain interactions, size, specific surface area, and the loading weight of nanoparticles (NPs) and their dispersion rate in the polymer matrix. [14][15][16] The efficient load transfer across the NP-matrix interface and the interactions of nanofiller with the polymer matrix are considered as essential parameters to improve the mechanical properties of the nanocomposite, where the nanofiller acts as a Pickering emulsion promoter. 14,15 The nanofiller can be positioned as the interface between the two immiscible phases, such that surface tension can be reduced by simultaneous reducing particle size for blends with island-sea type morphologies, in which the value of one of the components in the blend is greater than 60 wt %.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to the characteristics of PP, it is a primary structural material for 5G antennas, but it needs several modifications for effective and durable service [ 14 ]. Considering this, several reports that blend PP with PET could be the best choice to achieve excellent toughness, wear resistance, chemical stability, and thermal stability [ 15 , 16 ]. However, PET as a reinforcing phase with PP to make copolymer materials may be a convenient method to improve thermal stability, because a neat PP–PET blend usually exhibits rough, unstable phase morphology, and poor mechanical properties [ 17 ].…”
Section: Introductionmentioning
confidence: 99%